EFFECT OF EXAMINATION STRESS ON BLOOD CELL PARAMETERS OF STUDENTS IN A PAKISTANI MEDICAL COLLEGE - Qureshi, Faiyaz; Alam, Jane; Khan, Masood Ahmad; Sheraz, Ghazala (Journal of Ayub Medical College Abbottabad, 2002)
Background: Physiological studies show that stress can alter the blood cells parameters in healthy individuals. We tried to determine whether exams in medical schools are stressful enough to produce such changes. Methods: A randomized selection of female students from Women Medical College, Abbottabad, Pakistan, was carried out. After preliminary medical checkup blood samples were taken before and during exams. Students having temperature or high blood pressure at the start of study were excluded. Finally 37 students were included. Estimations of red blood cells, hematocrit, neutrophils, lymphocytes, eosinophils, monocytes, basophils and platelets were carried out. Results: Compared with pre-examination results the blood samples taken during exams showed a significant decrease in eosinophil, basophil, lymphocyte and monocyte count. An increase in platelet and neutrophil count was also observed. No significant changes were observed in red blood cell and hematocrit readings. Conclusion: It is concluded that examinations in medical schools are stressful enough to produce changes in blood cells parameters which include increase in neutrophils, and platelets, while eosinophils, monocytes basophils and lymphocytes decreased in number